PERTANIAN ORGANIK SEBAGAI JALAN ANUGERAH MENUJU KEUTUHAN CIPTAAN: Sebuah Upaya Membangun Ekoteologi Rasul Paulus Berdasarkan Roma 8 - Ance Sitohang (TANGKOLEH PUTAI, 2018)
The entire contents of the universe including humans experience interactions that are sometimes constructive but also destructive. Now the world seems to be in a destructive interaction. The entire universe is in a phase called the ecological crisis, namely environmental damage as the suffering of all God's creation. This suffering can be responded to Christianly through Paul's theology, which is God's saving gift that can reach all beings in the universe. Thus, Christians must do salvation work for all beings. One way that can be done is through organic farming, which is an effort to respect nature because nature has value in itself. This form of appreciation is expressed through our participation in nurturing this nature.